Risk assessment of heavy-metal contamination on vegetables grown in long-term wastewater irrigated urban farming sites in Accra, Ghana - Lente, I.; Keraita, Bernard N.; Drechsel, Pay; Ofosu-Anim, J.; Brimah, A.K. (Springer, 2012)
Assessment was done of heavy-metal contamination and its related health risks in urban vegetable farming in Accra. Samples of irrigation water (n=120), soil (n=144) and five different kinds of vegetable (n=240) were collected and analyzed for copper, zinc, lead, cadmium, chromium, nickel and cobalt. All water, soil and vegetable samples contained detectable concentrations of each of the seven heavy metals except for irrigation water which had no detectable chromium, cadmium and cobalt. All heavy-metal levels were below permissible limits except lead on vegetables which was 1.8-3.5 times higher. Health risk assessments showed for all elements that normal consumption of each of the vegetables assessed poses no risk. The highest hazard index obtained was 42 % for wastewater irrigated cabbage. Though within permissible limits, cabbage and ayoyo had the highest potential risk. Compared with previous studies on the same sites, the data show that the risk from heavy metals is less significance than that from pathogen contamination which has positive implications for risk mitigation.